Answer:
42
Step-by-step explanation:
Do the math:)
Answer:
yes it's right tick it right one
Answer:
Second option: ![(xy+x)(xy+x)](https://tex.z-dn.net/?f=%28xy%2Bx%29%28xy%2Bx%29)
Third option: ![(2x-3)(-3+2x)](https://tex.z-dn.net/?f=%282x-3%29%28-3%2B2x%29)
Fifth option:
Step-by-step explanation:
By definition, a perfect square trinomial can be obtained by squaring binomials.
Then:
![(a+b)^2=(a+b)(a+b)=a^2+2ab+b^2\\\\(a-b)^2=(a-b)(a-b)=a^2-2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3D%28a%2Bb%29%28a%2Bb%29%3Da%5E2%2B2ab%2Bb%5E2%5C%5C%5C%5C%28a-b%29%5E2%3D%28a-b%29%28a-b%29%3Da%5E2-2ab%2Bb%5E2)
Knowing this, to obtain a perfect square trinomial, the binomials that you multiply must be equals.
Therefore, the products result in a perfect square trinomial are:
![(xy+x)(xy+x)=(xy+x)^2=(xy)^2+2(xy)(x)+x^2=x^2y^2+2x^2y+x^2](https://tex.z-dn.net/?f=%28xy%2Bx%29%28xy%2Bx%29%3D%28xy%2Bx%29%5E2%3D%28xy%29%5E2%2B2%28xy%29%28x%29%2Bx%5E2%3Dx%5E2y%5E2%2B2x%5E2y%2Bx%5E2)
![(2x-3)(-3+2x)=(2x-3)^2=(2x)^2-2(2x)(3)+3^2=4x^2-12x+9](https://tex.z-dn.net/?f=%282x-3%29%28-3%2B2x%29%3D%282x-3%29%5E2%3D%282x%29%5E2-2%282x%29%283%29%2B3%5E2%3D4x%5E2-12x%2B9)
![(4y^2+25)(25+4y^2)=(4y^2+25)^2=(4y^2)^2+2(4y^2)(25)+25^2=16y^4+200y^2+625](https://tex.z-dn.net/?f=%284y%5E2%2B25%29%2825%2B4y%5E2%29%3D%284y%5E2%2B25%29%5E2%3D%284y%5E2%29%5E2%2B2%284y%5E2%29%2825%29%2B25%5E2%3D16y%5E4%2B200y%5E2%2B625)
Answer:
14x7=98
Step-by-step explanation:
First you see the line going down and there is the height 7 you can move that tiny triangle to the left where the parallelogram can be made into a rectangle.
all you need is to multiply base x height
base 14cm height 7cm pls brainliest
hope this helps!
2/9 - 7/12
First, multiply to find a common denominator. Multiply both pieces of the left fraction by 12, and both pieces of the right fraction by 9.
24/108 - 63/108 = -39/108 = -13/36
a= -13
b= 36